The Internet as a Source of Information for De Quervain's Tendinitis. (March 2015) - Heap, James C.; Dezfuli, Bobby; Bennett, David M.; Chapman, Eric; DeSilva, Gregory L.
Background: Many individuals are turning to the Internet for information about various health conditions, and in our study we evaluated the quality and readability of information on the internet about De Quervain's tendinitis. Methods: We chose the search terms "De Quervain's Tendinitis, " "De Quervain's Tenosynovitis, " and "De Quervain's Syndrome, " and entered them into the search engines "Google, " "Bing, " and "Yahoo" and compiled the search results. The websites were then evaluated and assigned a quality score, a Flesch-Kincaid (FK) reading level, and a subjective quality score. They were then grouped according to the search term used, search engine used and the order (priority) returned by the search engines. ANOVA analysis and pairwise comparisons of quality and readability among groups, as well as correlation analysis were performed. Results: The FK readability average was 10.3, above the recommended level. The search term De Quervain's tenosynovitis returned the highest objective quality results. There was no statistical difference found between the different search engines. The first 10 results from the searches were of higher quality than results 11–20, and there was a positive correlation between objective and subjective quality scores but no correlation between readability and objective quality. Conclusions: We concluded that quality information about De Quervain's tendinitis is available on the internet and is most likely to be found using the search term De Quervain's tenosynovitis and in the first 10 results of an internet search. However, most information is written above the recommended 6th grade reading level.